How to interpret high levels of distress when using the Distress Thermometer in the long-term follow-up clinic? A study with Acute Lymphoblastic Leukemia survivors. (3rd April 2017) - Pépin, A. J.; Lippé, S.; Krajinovic, M.; Laverdière, C.; Michon, B.; Sinnett, D.; Sultan, S.
ABSTRACT: Objectives: Recent guidelines recommend to assess emotional distress in pediatric oncology during treatment and in after care. One tool used to do this is the distress thermometer (DT), a simple tool which has almost exclusively been studied in its screening abilities. Given its increased used as a measure of distress per se, it is necessary to document its concurrent validity. The goal of this study was to identify clinical domains (eg, depression, anxiety) and individual symptoms associated with pediatric cancer survivors' rating on the DT.Participants: To do so we used data collected from 84 young (≤18 years old), and 120 older (>18 years old) survivors who were treated for pediatric leukemia.Methods: Participants responded to self-report questionnaires as part of a research visit.Results: Results from stepwise regressions show that in the younger group, high scores on the thermometer were associated with higher negative affectivity only. In adults, high scores were associated with higher anxiety, higher negative affectivity, and lower positive affectivity. When exploring associations with individual items, we found that the main emotional tone reflected by the thermometer score was anxiety.Conclusions: Interpreting ratings on the thermometer should probably focus on anxiety in childhood cancer survivors. This widely used tool also does not measure the same domains in young versus older survivors, so that age groups should be considered separately in future work.